Blood levels of copper, manganese, selenium, and zinc are positively associated with cognitive function and academic performance in adolescents - Rahman, Abdur; Rao, Muddanna; Aldughpassi, Ahmed; Jallad, Reem; Shaban, Lemia (Frontiers in Nutrition, 2025)
BackgroundMicrominerals copper (Cu), manganese (Mn), selenium (Se), and zinc (Zn) regulate neuronal signaling and brain function. Deficiencies of these minerals are common in adolescents due to unhealthy eating habits. We investigated the association between micromineral levels and cognitive function and academic performance in a nationally representative sample of adolescents.MethodsAdolescents (N = 1,370; 11–14 years) were selected from public middle schools in Kuwait, using cluster random sampling. Data on various covariates were collected through a questionnaire from the subjects and their parents. Blood micromineral levels were determined using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Cognitive function was evaluated through the Raven’s Standard Progressive Matrices test and academic performance data were taken from the school records.ResultsMedian (IQR) blood levels of microminerals (μg/dL) were as follows: Cu, 22.5 (15.2, 33.0); Mn, 6.0 (3.5, 10.6); Se, 34.2 (22.1, 52.5); Zn, 163.5 (118.5, 233.5). On average, SPM score was higher by 5 points in adolescents with mineral levels above the median, compared to those with levels below median (p < 0.05). Academic performance in adolescents with micromineral levels in Q1 was lower by an average of seven-percentage points compared to those in Q4 (p < 0.01). Multivariable regression analysis showed positive association (p < 0.01) with both cognitive function and academic performance, whether the micromineral levels were used as continuous variable or as quartiles.ConclusionIn this cohort, blood micromineral levels are positively associated with cognitive function and academic performance. Improving micromineral status by public health intervention is strongly warranted, as academic performance during early-life education has implications on the later-life socio-economic status.